Intra‐Intermolecular Palladium‐Catalyzed Domino Reactions of Glycine Allylamides for the Synthesis of Diversely Functionalized Piperazinones. Issue 19 (27th May 2015) - Broggini, Gianluigi; Beccalli, Egle M.; Borelli, Tea; Brusa, Filippo; Gazzola, Silvia; Mazza, Alberto
Abstract: Easily accessible N ‐tosylglycine allylamides have been converted into diversely functionalized piperazinone derivatives by inter‐intramolecular oxidative domino palladium‐catalyzed reactions. Aminochlorination and aminoacetoxylation processes were achieved by employing CuCl2 and PhI(OAc)2 as the oxidizing agents to give 5‐chloromethyl‐ and 5‐acetoxymethyl‐substituted piperazinones, respectively. Abstract : Inter‐intramolecular domino palladium‐catalyzed reactions of N ‐tosylglycine allylamides were used to access piperazinones with functional groups that can undergo further transformations. Aminochlorination and aminoacetoxylation processes were achieved by using CuCl2 and PhI(OAc)2 as oxidizing agents to give 5‐chloromethyl‐ and 5‐acetoxymethyl‐substituted piperazinones, respectively.